NEGATIVE PERSONALITY PREDISPOSITIONS AS PREDICTORS OF PSYCHOPATHIC TRENDS AMONG NON-FORENSIC POPULATION - Habib, Shazia; Shahida Batool, Syeda (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the relationship and predictive strength of negative personality predispositions in psychopathic trends among non-forensic population. Methodology: The current research was carried out in different cities of Punjab province (viz., Lahore, Islamabad, Multan, Sargodha and Faisalabad). The sample consisted of 400 participants from general population. Purposive sampling strategy was used for sample selection. Negative personality predispositions were measured by using Adult Personality Assessment Questionnaire (Adult PAQ; Rohner, 2005) and psychopathic trends were measured by using Self- Report Psychopathy Scale-III-Revised (SRP-III-R; Paulhus, Neuman & Hare, 2009). The data were analyzed by SPSS version 21. Statistical analyses were carried out through correlation analysis, multiple step wise regression analyses and multivariate analysis of variance (MANOVA). Results: There were 400 (221 men; 179 women) participants with age ranging between 20-44 years. Primary and secondary psychopathic trends were positively correlated with negative personality predispositions (r= .37, p <.01; r= .39, p <.01) respectively. The stepwise regression analyses revealed that negative personality predispositions hostility/aggression and negative world view significantly predicted primary psychopathic trends (R2= .15, p <0.01; R2= .17, p <0.01) respectively; whereas, hostility/aggression, negative self-esteem and dependency significantly predicted secondary psychopathic trends (R2= .17, p< 0.01; R2= .22, p <0.01; R2= .23, p <0.01) respectively. Conclusion: Negative personality predispositions are substantial risk factors in the development of psychopathy among non-forensic population.